Identification of TP53 mutated group using a molecular and immunohistochemical classification of endometrial carcinoma to improve prognostic evaluation for adjuvant treatments. Issue 5 (12th March 2020) - Beinse, Guillaume; Rance, Bastien; Just, Pierre-Alexandre; Izac, Brigitte; Letourneur, Franck; Saidu, Nathaniel Edward Bennett; Chouzenoux, Sandrine; Nicco, Carole; Goldwasser, François; Batteux, Frederic; Durdux, Catherine; Chapron, Charles; et al.
Abstract : Introduction: Molecular classification of endometrial carcinoma has been proposed to predict survival. However, its role in patient management remains to be determined. We aimed to identify whether a molecular and immunohistochemical classification of endometrial carcinoma could improve decision-making for adjuvant therapy. Methods: All consecutive patients treated for endometrial carcinoma between 2010 and 2017 at Cochin University Hospital were included. Clinical risk of relapse was based on European Society for Medical Oncology-European Society of Gynaecological Oncology-European SocieTy for Radiotherapy & Oncology (ESMO-ESGO-ESTRO) consensus. The clinical event of interest was event-free survival. Formalin-fixed paraffin-embedded tissue samples were processed for histopathological analysis and DNA extraction. The nuclear expression of mismatch repair and TP53 proteins was analyzed by immunohistochemistry. Next-generation sequencing of a panel of 15 genes including TP53 and POLE was performed using Ampliseq panels on Ion Torrent PGM (ThermoFisher). Tumors were allocated into four molecular groups using a sequential method based on next-generation sequencing and immunohistochemistry data: (1) POLE /ultramutated-like; (2) MSI/hypermutated-like (mismatch repair-deficient); (3) TP53 -mutated (without POLE mutations or mismatch repair deficiency); (4) not otherwise specified (the remaining tumors). Results: 159 patients were included; 125 tumors were available for molecular characterization and distributed as follows: (1) POLE /ultramutated-like: n=4 (3%); (2) MSI/hypermutated-like: n=35 (30%); (3) TP53 -mutated: n=30 (25%); and (4) not otherwise specified: n=49 (42%). Assessing the TP53 status by immunohistochemistry only rather than next-generation sequencing would have misclassified 6 tumors (5%). TP53 -mutated tumors were associated with poor prognosis, independently of International Federation of Gynecology and Obstetrics (FIGO) stage and histological grade (Cox-based adjusted hazard ratio (aHR) 5.54, 95% CI 2.30 to 13.4), and independently of clinical risk of relapse (aHR 3.92, 95% CI 1.59 to 9.64). Among patients with FIGO stage I–II tumors, 6 (38%) TP53 -mutated tumors had low/intermediate clinical risk of relapse and did not receive adjuvant chemotherapy or radiotherapy. Conclusion: Endometrial carcinoma molecular classification identified potentially under-treated patients with poor molecular prognosis despite being at low/intermediate clinical risk of relapse. Consideration of molecular classification in adjuvant therapeutic decisions should be evaluated in prospective trials.